Cardano : The Gambling Scholar - Ore, Oystein, 1899-1968 (Book collections on Project MUSE., 2017)
Cardano, next to Vesalius the greatest physician of his day, was also a devoted and skilled gambler who played for personal pleasure and profit. His mathematical genius enabled him to devise simple rules of probability for his own benefit and for his gambling contemporaries. These he collected in his Book on Games of Chance and embellished them with essays on the tricks of cheats and kibitzers, as well as on psychological rules of play. In this biography of a stormy Renaissance personality, Cardano's gambling studies are deciphered for the first time, and a translation of the Book on Games of Chance is appended. Originally published in 1953. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.